Development of Dam-Break Model Considering Real Case Studies with Asymmetric Reservoirs - Ahmad Ferdowsi; Mahmood Nemati; Saeed Farzin (Computational Engineering and Physical Modeling, 2021)
Dam-break flow is known as one of the most horrible phenomena. Some hypothetical reservoir geometries were evaluated in literature, but in nature, each reservoir has a unique geometry. In the present research, dam-break flow was studied based on different reservoir geometries using FLOW-3D. Six reservoirs were considered: reservoirs R1 and R2 belonged to Mahabad Dam (Iran) and Tignes Dam (France), with asymmetric reservoirs, respectively; reservoirs R3 and R4 had symmetrical trapezoidal reservoirs with angles 30 and 45 degrees, respectively; reservoir R5 had a rectangular shape, extending from one side; and reservoir R6 had a long reservoir, which also was used to verify FLOW-3D. The model performance was verified by experimental results and FLUENT model in literature. Results showed FLOW-3D with mesh sizes 30×30×30 mm and k-ɛ turbulence model outperformed FLUENT, based on R2, RMSE, and MAE. The results of water levels and flow velocities at five points proved that dam-break flow could vary from one dam to another, considering reservoir geometry. Peak water levels and velocities have been measured to show how reservoir geometry could cause catastrophic flow.